The Effect of Backchannel Communication in Developing Students’ Critical Thinking Skills - Rathakrishnan, Mohan; Raman, Arumugam; Singh, Manvender Kaur Sarjit; Lee, Jun Choi (Academic Research Publishing Group, 2018)
The purpose of this study is to examine the effect of backchannel communication in developing students‟critical thinking skill: macro and micro critical thinking.There are many tools in backchannel communication (BC). Padlet has been used as one of backchannel communication in this research.There are seventy students from two classes (Class X and Class Z) involved as sample in this study.Quasi- experimental research design applied in this research. Class X was selected as the experimental group (using padlet online discussion) and Class Z became the control group (classroom discussion) while learning Critical Thinking subject. Padlet online discussion was used as tool to plot discussion in a group on the topic given by the teacher. The finding shows that students who used back channel communication showed greater macro critical thinking level than to those who did not use back channel communication. While for students who used BC did not show greater critical thinking level than to those who did not use BC.This study will contribute to the body of knowledge on technologies for learning and online learning. This will allow better understanding on how technology can facilitate learning especially critical thinking.